PENGARUH SUKU BUNGA DAN INFLASI TERHADAP JUMLAH TABUNGAN DI KALIMANTAN BARAT TAHUN 2004-2011 - B01107031, Arif Amrullah (Jurnal Curvanomic, 2015)
In this thesis the goal of the research is to investigate and analyze the effect of interestrate and inflation savings to total savings in West Kalimantan. Research method uses quantitative method to determine the effect of inflation oninterest rates and the amount of savings in West Kalimantan. the data for the analysis in adata-quarter of the period 2004 – 2011. The analysis technique used is multiple regression,while the statistical test using t tests to examine the effect of variable and F test to examinethe effect of variables simultaneously. Research results find that interest rates significantly affect the amount of savings,while inflation has a negative direction on savings in West Kalimantan. F test showed thatFhit> F which have a weak 1.293206 > 3.33 which means that interest rates and inflationtogether - at no significant effect on the amount of savings in West Kalimantan. on the resultsof the t test results obtained in interest rates and inflation have weak relationship to saving. Keywords: Total Saving, Interest Rate, and Inflation.